PENGEMBANGAN MODUL BERBANTUAN GEOGEBRA PADA PERKULIAHAN GEOMETRI TRANSFORMASI - Ratri Isharyadi; Marfi Ario (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
This study aims to develop and find out the quality of teaching materials in the form of teaching modules assisted by the geogebra program on transformational geometry lectures. The Geogebra-assisted transformation geometry module is structured systematically and accompanied by steps to solve transformation problems using Geogebra. This type of research is development research (Research and Development / R & D). The development model is 4D which consists of four stages, namely defining, designing, developing and disseminating. In this study, only three steps were carried out, namely the defining, the design, and the development stage. The research instrument is a module validation sheet. The product assessment was carried out by 3 validators consisting of 2 material experts and 1 media expert who was a lecturer in the mathematics education study program. The results showed that the assessment of the two validators of material experts on the geogebra-assisted transformation geometry module developed had an average total score of 3.38 with very good criteria, while for validators media experts had an average total score of 3.21 with very good criteria. Very good criteria from the results of the validation of media experts and material experts showed that the geometry module of geogebra-assisted transformation was valid and suitable for use as teaching material in lectures.